2019
DOI: 10.18203/2319-2003.ijbcp20190564
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study of antibiotics in infectious diseases in a tertiary care hospital

Abstract: Background: Infectious diseases represent a major cause of mortality and morbidity in India. Irrational use of antibiotics can cause increase adverse drug reaction, leading to antibiotic resistance and increase in the treatment cost. Hence pattern of use of antibiotics need to be studied, therefore the aim of our study is to observe the antibiotics prescription pattern and drug utilization in department of medicine indoor patients at our tertiary care hospital.Methods: This was a prospective observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…( to 60 years old (32%), 20 to 40 years old (29%), and 20 to 30 years old (29%), while patients aged 20 to 30 years old were prominent in one of the investigations. (Rangdal K et al, 2019). The majority of patients in the Solanki N et al 2021 research were between the ages of 50 and 79 years, with proven co-morbidities; however, the majority of patients in the current study were between the ages of 40 and 80 years, which con rmed our study results.…”
Section: Discussionsupporting
confidence: 81%
“…( to 60 years old (32%), 20 to 40 years old (29%), and 20 to 30 years old (29%), while patients aged 20 to 30 years old were prominent in one of the investigations. (Rangdal K et al, 2019). The majority of patients in the Solanki N et al 2021 research were between the ages of 50 and 79 years, with proven co-morbidities; however, the majority of patients in the current study were between the ages of 40 and 80 years, which con rmed our study results.…”
Section: Discussionsupporting
confidence: 81%
“…In our study 257 cases were reviewed among which 46.77% were males and 53.23% were females in MRD group, out of 124 cases and 53.38% were males and 46.62% were females in ICU group, out of 133 cases. Similarly, a study carried out by Bimba et al showed 57.8% males and 42.2 % females inpatients whereas another study also suggests similar findings [14][15]. The mean age of patients in MRD group was 56.16 and in ICU group was 56.00 years.…”
supporting
confidence: 56%
“…Similarly a study carried out by Rangdal et al, showed 44% was males and 56% was females. 8 Another study suggests that 58% were male and 42% were females. 9 The mean age patients was 56.16, out of which mean age of males was 56.95±21.34 years and females was 55.48±20.52 years in MRD group and the mean age patients were 56.00 years, out of which mean age of males was 57.75±14.49 and females was 54.37±16.65 years in MICU group.…”
Section: Discussionmentioning
confidence: 99%